GENETIC AND PHENOTYPIC PARAMETERS FOR GROWTH TRAITS OF NILI-RAVI BUFFALO HEIFERS IN PAKISTAN - P. Akhtar; U. Kalsoom; S. Ali; M. Yaqoob; K. Javed; M. E. Babar; M. I. Mustafa; J. I. Sultan (Journal of Animal and Plant Sciences, 2012)
Data on body weights at different ages of 624 Nili Ravi buffalo heifers from 243 dams and sired by 48 sires kept at LES, Bahadurnagar, Okara, Pakistan were collected from 1989 to 2002 and analyzed by using DFREML (Derivative Free Restricted Maximum Likelihood) in this study. Average weights at birth, weaning, yearling, Pre-weaning average daily gain were 35.86±4.30 kg with CV of 11.99%, 66.12±9.16 with CV 13.85%, 145.82±19.50 with CV of 13.37%, 316.47±88.33 g for Nili-Ravi female calves, while average post-weaning daily gain was 297.66±31.03 g. Average weight at 2 years of age in heifers was 240.05±25.10 kg and average 3 years weight was 329.73±23.17 kg. ANOVA indicated significant effect of birth year, season of birth, age and weight of dam on the growth traits. Maximum weight was observed in spring season, while minimum weight was obtained in winter season. The maximum heritability was 0.25±0.14 for birth weight while the minimum heritability was 0.16±0.75 for yearling weight. The heritability estimates for all growth traits were moderate to high suggesting that selection might be a good criterion for improvement. The phenotypic correlations ranged from 0.29±0.19 between birth weight and weight at 36 month’s age and 0.76±0.16 between weaning weight and weight at 12 month’s age. The maximum environmental correlation was 0.83±0.20 between 12 months weight and weight at 24 months of age while it was minimum as 0.23±0.11 between weaning weight and weight at 36 months of age. The highest genetic correlation was 0.62±0.09 between birth weight and weight at 24 months of age whereas minimum genetic correlation was 0.25±0.12 between 12 months weight and weight at 36 months of age. In general correlations were fairly large and positive indicating that selecting one trait will positively affect the other trait.
Keywords: Genetic parameters; Growth traits; Buffalo heifers; Pakistan